Service management and marketing principles: competing in the service economy - Kandampully, Jay; Solnet, David J. (London Routledge, 2024)
This book analyses management and marketing challenges in the service and experience economy and provides insights into how marketers and managers can strike a balance between supply, demand, price, and quality and leverage technology for operational efficiency and to better manage customer service and expectations. Through the coverage of critical foundational topics, from how value is created; the evolution of global economies from goods, services to experiences; foundations of customer-centric management; managing service workers; integrating human touch with high-tech service; and many others, the authors provide a holistic understanding of management in a complex, globally interconnected world.
Keywords: Area Studies; Business; Economics; Finance